Pengaruh Persepsi Harga, Citra Merek, Social Media Influencer Terhadap Keputusan Pembelian Lipstik Maybelline (Studi pada Masyarakat Kota Pekanbaru) - Putri Elda Rentica; Ainun Mardiah (Yayasan Almanar Pujud, 2025)
This study aims to determine the effect of price perception, brand image and social media influencers on the purchasing decision of Maybelline lipstick in the community in Pekanbaru city. This type of research is quantitative research using multiple linear regression methods. The number of samples in this study was 96 respondents selected using the purposive sampling method. Data collection was carried out by distributing questionnaires to respondents. The research data was analyzed using the SPSS V.25 program. The results of this study indicate that partially price perception, brand image and social media influencers have a positive and significant effect on the purchasing decision of Maybelline lipstick. The results of the Simultaneous test show that price perception, brand image and social media influencers have a Positive and Significant influence on the purchasing decision of Maybelline lipstick. From the table above, it can be seen that the R square value is 0.640, that the Purchase Decision variable can be explained by the variables Price Perception, Brand Image and Social Media Influencer by 64.0%, while the remaining 34.0% are other variables that are not examined in this study.